Pengembangan Media Renewwable Energy Houseminiatur Untuk Meningkatkan Kemampuan Problem solving Dalam Pembelajaran Ipas Siswa Kelas IV Madrasah Ibtidaiyah - Widji Agustin Ningsih; Nurhaningtyas Agustin (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to develop a learning media called Renewable Energy House Miniature to improve students’ problem solving skills in IPAS learning for fourth grade elementary school students. The research uses a Research and ’evelopment (R&D) method with the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The data were collected through observation, interviews, validation sheets, questionnaires, and tests. The results show that the de’eloped media meets the criteria of validity, practicality, and effectiveness. The use of Renewable Energy House Miniature helps students understand abstract concepts of renewable energy through direct observation and experimentation, thereby improving their engagement and problem solving skills. Therefore, this media is feasible to be used as an innovative learning tool in IPAS learning at the elementary level.